INCREASING THE STUDENTS’ CREATIVITY THROUGH MOSAIC ACTIVITY USING PLASTIC BAG WASTE AS MEDIA AT SD NEGERI 3 MUARA BATU KABUPATEN ACEH UTARA - Nofriati, Eli; Junaidi Putri, Dwi Adhinda; Zulkarnaini, Zulkarnaini (Journal of English Education and Social Science, 2024)
The aim of the research was to increase the students’ creativity in learning SBDP subject. In this case, the students had low creativity and difficulties in making the artworks when they learn SBDP. So, here the researcher chose the mosaic activity by using plastic bag waste as media in order to help the students in increasing their creativity. As the research methodology, the researcher classroom action research and used qualitative descriptive approach in this research and the subject of the research was the fifth grade students of SD Negeri 3 Muara Batu Kabupaten Aceh Utara. The sum of the research subjects were 20 students. In collecting the data, the researcher used some research instruments such as observation sheets, test and questionnaire. Based on the data analysis, it was found the result 1). The students’ activity in leaning process was increased from the cycle 1 (60%) to be 80% in cycle 2. 2). The teacher’s performance during the teaching process in cycle 1 was 75% increased to 85% in cycle 2. 3). the students’ creativity in making artworks had increased from 60 in cycle 1 to be 85 in cycle 2. 4). The students gave positive responses toward the use of plastic bag waste as media in making artworks through mosaic activity . The students also were be more active during the teaching learning process. It could be concluded that the use of plastic bag waste as media through mosaic activity could increase the students’ creativity in in learning SBDP subject.